(untitled) (Bangladesh Journal of Neuroscience, 2016)
Background: A high proportion of patients suffering from an acute stressful condition asuch as stroke or myocardial infarction may develop hyperglycemia even in the absence of a preexisting diagnosis of diabetes. The study evaluates the effect of hyperglycemia in the severity and outcome during the acute phase of stroke. Methods: This was a descriptive cross-sectional study. Baseline variables (eg: age, sex, smoking, hypertension, diabetes OHA/insulin) and outcome measures (mortaily, disability) were statistically analysed and compared with a control group of 50 patients of acute ischemic storke without admission hyperglycemia. Result: the base line characteristis of the two patient groups were comparable. The 1st week mortality was 16% in case group and 2% in the control group. the 30 days mortality in the case group and control group was 28% and 12% respectively, 58.33% were disabled & dependent in the hyperglycemia group, in comparison to 36.36% subjects in the control group. Conclusion: Admission hyperglycemia seems worsen the outcome and functional disability during the acute phase of Ischemic stroke. Admission glucose level is an important risk factor and should be immediately treated to reduce morbitidity & mortality in acute Ischemic stroke cases Bangladesh Journal of Neuroscience 2016; Vol. 32 (1): 28-33